First record of Leucophaeus atricilla (Linnaeus, 1758) on the southern coast of Santa Catarina - Samira Effting; Pedro Volkmer De Castilho (Acta Biológica Catarinense, 2023)
On November 8, 2021, an adult individual of the laughing gull (Leucophaeus atricilla) was observed on a stretch of sandy beach in the municipality of Imbituba, State of Santa Catarina (SC), between the beaches of Vila and Itapirubá Norte. The second record took place on November 12, 2021, in the municipality of Laguna, also in SC. These are the first records of this species for the State, on the southern coast of Brazil, demonstrating the potential for southern displacement of Leucophaeus atricilla, pointing to a possible expansion of its non-reproductive distribution area on the Brazilian coast. The present observations can serve as a pioneer indication of the establishment of new populations in this new region of occurrence.